Über Verteilung der Basisclcmenlen in den freien Zahlenhalbgruppen. I - Cibulskytė, D. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Цибульските. О распределении образующих элементов в свободных числовых полугруппах. ID. Cibulskytė. Laisvos skaitinės pusgrupės generuojančių elementų pasiskirstymo klausimu. I